Pengukuran Kualitas Website Fakultas Dakwah Dan Komunikasi Menggunakan Metode Webqual - Fathiyah Nopriani (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2022)
The website of the Faculty of Da'wah and Communication at the State Islamic University of Raden Fatah Palembang should have good quality to provide information as a form of service to its users, but since the development, improvement, and addition of features, the service quality of the website has not been known, because sofar no quality measurement has been carried out. service. The purpose of this study was to find out how much the quality level of the website of the Faculty of Da'wah and Communication of Raden Fatah State Islamic University Palembang used the Webqual method. The dimensions used in the measurement include usability, information quality, service interaction quality. The results of the analysis show that the Usability, Information Quality, Interaction Quality variables have a significant value on User Satisfaction which has no effect on Usability because the significant value is greater than 0.05.Keywords: Usability, information quality; service interaction quality, Interaction Quality; User Satisfaction.AbstrakWebsite Fakultas Dakwah dan Komunikasi Univeristas Islam Negeri Raden Fatah Palembang harusnya memiliki kualitas yang baik untuk memberikan informasi sebagai wujud pelayanan kepada penggunanya, namun sejak pengembangan, perbaikan, dan penambahan fitur, kualitas layanan website tersebut belum diketahui, karena selama ini belum pernah dilakukan pengukuran kualitas layanan. Tujuan penelitian ini untuk mengetahui seberapa besar tingkat kualitas website Fakultas Dakwah dan Komunikasi Univeristas Islam Negeri Raden Fatah Palembang dengan menggunakan metode Webqual. Dimensi yang dugunakan dalam pengukuran meliputi kemudahan pengguna (usability), kualitas informasi (information quality), kualitas interaksi pelayanan (servicie nteraction quality). Hasil analisis didapatkan variabel Usability, Information Quality, Interaction Quality nilai signifikan terhadap User Satisfaction yang tidak berpengaruh adalah Usability karena nilai signifikan nya lebih besar dari 0,05.